DEVELOPMENT AND TESTING OF ARROWROOT (MARANTHA ARUNDINACEA L.) GRINDING MACHINE - Pascua, Alexander (International Journal of Engineering Technologies and Management Research, 2018)
An arrowroot grinding machine was developed and evaluated in terms of functional performance and cost effectiveness. The model consists of different component assembly parts such as transmission, rasper, crusher and base frame. It is powered by a 7.5 hp gasoline engine. Its salient features such as: 1) made of locally available food grade materials, 2) portable and 3) can be operated by a single person, give it the edge over other existing machines in attaining effective processing. The model has an overall cost of P65,000.00. The effects of different factors which include the machine speed, tuber size and tuber maturity on the response variables such as power requirement, processing time, machine capacity and efficiency (percent starch recovery) were observed. RSReg and Response Surface Methodology (RSM) were used to determine the effect of the treatment factors and optimum performance of the machine; respectively. Experimental runs using Box and Behnken design with three levelincomplete factorial designs were conducted. Results revealed that change on the levels of treatment factors significantly affect most of the response variables. Data obtained from the response variables mostly fit the linear and quadratic regression models. Results of evaluation revealed that the model is capable of grinding arrowroot tubers with average power consumption of 0.85 kW, processing time of 7.85 minutes, capacity of 46.6 kilograms per hour and efficiency (starch recovery) of 16.6%. Verification tests indicated that the actual values of responses were relatively close to the predicted values. Further, financial analysis showed that the machine was economically feasible for small scale farm arrowroot production with payback period of 0.343 years or 4 months and 3 days, break-even point of around 350 kg per year and benefit cost ratio of 1.96.